The Fractalkine Receptor CX3CR1 Links Lymphocyte Kinetics in CMV-Seropositive Patients and Acute Myocardial Infarction With Adverse Left Ventricular Remodeling - Spray, Luke; Park, Catherine; Cormack, Suzanne; Mohammed, Ashfaq; Panahi, Pedram; Boag, Stephen; Bennaceur, Karim; Sopova, Kateryna; Richardson, Gavin; Stangl, Verena M.; Rech, Lavinia; Rainer, Peter P.; et al. (Frontiers in Immunology, 2021)
Aims: Latent cytomegalovirus (CMV) infection is associated with adverse cardiovascular outcomes. Virus-specific CX3CR1+ effector memory T-cells may be instrumental in this process due to their pro-inflammatory properties. We investigated the role of CX3CR1 (fractalkine receptor) in CMV-related lymphocyte kinetics and cardiac remodeling in patients with ST-elevation myocardial infarction (STEMI) undergoing primary percutaneous coronary intervention (pPCI). Methods and results: We retrospectively analysed lymphocyte count, troponin, and survival in 4874 STEMI/pPCI patients, evaluated lymphocyte kinetics during reperfusion in a prospective cohort, and obtained sequential cardiac MRI (cMRI) to assess remodeling. Pre-reperfusion lymphopenia independently predicted mortality at 7.5 years. Prior to reperfusuon, CCR7+ T-lymphocytes appeared to be depleted. After reperfusion, T-lymphocytes expressing CX3CR1 were depleted predominantly in CMV-seropositive patients. During ischaemia/reperfusion, a drop in CX3CR1+ T-lymphocytes was significantly linked with microvascular obstruction in CMV+ patients, suggesting increased fractalkine-receptor interaction. At 12 weeks, CMV+ patients displayed adverse LV remodeling, and post-reperfusion loss of CX3CR1+ T-cells predicted more extensive microvascular obstruction on cMRI. Conclusion: We show that lymphopenia occurs before and after reperfusion in STEMI by different mechanisms and predicts long-term outcome. In CMV+ patients, increased fractalkine induction and sequestration of CX3CR1+ T-cells may contribute to adverse remodeling, suggesting a pro-inflammatory pathomechanism which presents a novel therapeutic target.